2022
DOI: 10.3390/jof8101111
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Associated with Cryptococcosis: A New Challenge during the Pandemic

Abstract: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a great threat to global health. In addition to SARS-CoV-2 itself, clinicians should be alert to the possible occurrence of co-infection or secondary infection among patients with COVID-19. The possible co-pathogens include bacteria, viruses, and fungi, but COVID-19-associated cryptococcosis is rarely reported. This review provided updated and comprehensive information about this rare clinical entity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“… 48 In the present study, six isolates were MDR, of which four were reported in cryptococcal fungemia, indicating the severity of cryptococcemia. 49 The high numbers of NWT isolates were reported against amphotericin B (8.96%), similar to a previous study reported from China, in which 8.6% of isolates were NWT. However, the proportion of NWT isolates against 5-flucytosine and fluconazole in the present study is lower than the previously published literature from China.…”
Section: Discussionsupporting
confidence: 88%
“… 48 In the present study, six isolates were MDR, of which four were reported in cryptococcal fungemia, indicating the severity of cryptococcemia. 49 The high numbers of NWT isolates were reported against amphotericin B (8.96%), similar to a previous study reported from China, in which 8.6% of isolates were NWT. However, the proportion of NWT isolates against 5-flucytosine and fluconazole in the present study is lower than the previously published literature from China.…”
Section: Discussionsupporting
confidence: 88%
“…Overall, cryptococcosis in COVID-19 patients is not as frequent compared to other fungal infections such as mucormycosis 70 and aspergillosis, 71 widely reported in the literature, in COVID-19 patients, although it can still be life-threatening in light of the high mortality, ranging between 50% and 65%. 23 , 50 , 72 , 73 Our analysis showed that the majority of patients were men and around 60 years of age, and in addition, it was determined that both male sex and age are risk factors associated with mortality. The male sex is related to the incidence, severity, and mortality of COVID-19.…”
Section: Discussionmentioning
confidence: 88%
“…Twenty-one patients had HIV infection in reports described by US researchers [57]. Chan and reseachers [58] reported 18 cases of COVID-19 infections associated with cryptococcosis, isolating C. neoformans and C. laurentii in their case series; these researchers, in summary, emphasized that COVID-19-associated cryptococcosis is uncommon; however, it may be underestimated due to underdiagnosis.…”
Section: Reports Of Immunosuppression In Cases Of Sars-covmentioning
confidence: 96%